Prof. M. V. Deshpande-An Educationist - ., . (Journal of Engineering Education Transformations, 1996)
Born on 31st Oct. 1916 at Pune, Prof. M. V. Deshpande graduated from Govt. College of engineering Pune in 1938 (in Electrical & Mechanical Engineering). After training of 2 years, he joined Govt. College of Engineering, Pune in 1940 as a demonstrator; later worked as lecturer. In 1948, he got postgraduate scholarship in U.s.A .. He completed M. S. in 1950 from University Illinois. After return from U.s.A.